2017
DOI: 10.3390/rs9111096
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness (of Insects) Drives the Use of Acoustic Space in the Tropics

Abstract: Acoustic ecology, or ecoacoustics, is a growing field that uses sound as a tool to evaluate animal communities. In this manuscript, we evaluate recordings from eight tropical forest sites that vary in species richness, from a relatively low diversity Caribbean forest to a megadiverse Amazonian forest, with the goal of understanding the relationship between acoustic space use (ASU) and species diversity across different taxonomic groups. For each site, we determined the acoustic morphospecies richness and compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 45 publications
1
81
0
8
Order By: Relevance
“…It would be unrealistic to assume that an acoustic index could be equally sensitive to sound types that vary dramatically in spectral or temporal occupancy (Gasc, Pavoine, Lellouch, Grandcolas, & Sueur, 2015). In the case of this acoustic community, acoustic indices offered a much better window into overall sound type occupancy, which has recently been linked to sound type richness in terrestrial tropical habitats (Aide, Hern andez-Serna, Campos-Cerqueira, Acevedo-Charry, & Deichmann, 2017). In a similar study on the soundscapes of temperate ponds, Desjonqu eres et al (2015) found that only the acoustic index Acoustic Richness was marginally correlated with sound type richness (correlation of 0.2) and abundance (correlation of 0.19), once controlling for the SNR of the sound types.…”
Section: Acoustic Index-and Sound Type-based Soundscape Measurementsmentioning
confidence: 99%
“…It would be unrealistic to assume that an acoustic index could be equally sensitive to sound types that vary dramatically in spectral or temporal occupancy (Gasc, Pavoine, Lellouch, Grandcolas, & Sueur, 2015). In the case of this acoustic community, acoustic indices offered a much better window into overall sound type occupancy, which has recently been linked to sound type richness in terrestrial tropical habitats (Aide, Hern andez-Serna, Campos-Cerqueira, Acevedo-Charry, & Deichmann, 2017). In a similar study on the soundscapes of temperate ponds, Desjonqu eres et al (2015) found that only the acoustic index Acoustic Richness was marginally correlated with sound type richness (correlation of 0.2) and abundance (correlation of 0.19), once controlling for the SNR of the sound types.…”
Section: Acoustic Index-and Sound Type-based Soundscape Measurementsmentioning
confidence: 99%
“…)] and sampling a wider range of taxonomic groups (Aide et al . ). We consider camera trapping and acoustic monitoring to be complementary in terms of taxonomic groups and advocate the use of both methods where possible.…”
Section: Advantages Of Passive Acoustic Monitoringmentioning
confidence: 97%
“…, Aide et al . , Rankin & Axel ), yet there is no consensus to date as to which are most effective, primarily due to the difficulties in generalizing across taxa and ecosystems (Buxton et al . ).…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary limitation to this method is the need for large amounts of digital storage and the development of time demanding acoustic pattern recognition models. Aide et al (2017) suggest a potential alternative to these models for generalizing the relative diversity between sites: Acoustic Space Use (ASU). ASU is the percentage of acoustic space, comprised of both time and frequency ranges, used by the collective sound of the faunal community.…”
Section: Introductionmentioning
confidence: 99%